2022
DOI: 10.3389/fonc.2022.1069635
|View full text |Cite
|
Sign up to set email alerts
|

Soluble HLA peptidome: A new resource for cancer biomarkers

Abstract: Using circulating molecular biomarkers to screen for cancer and other debilitating disorders in a high-throughput and low-cost fashion is becoming increasingly attractive in medicine. One major limitation of investigating protein biomarkers in body fluids is that only one-fourth of the entire proteome can be routinely detected in these fluids. In contrast, Human Leukocyte Antigen (HLA) presents peptides from the entire proteome on the cell surface. While peptide-HLA complexes are predominantly membrane-bound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The peptidome -consisting of thousands of peptides: remnants of protein degradation; specific precursor-derived peptides such as hormones, cytokines, or growth factors; and translation products of small open reading frames (smORFs) [16] responds dynamically to changes in the body, providing a rich source of potential biomarkers. This results in the rapid expansion of peptidomics research observed in recent years [17,18], demonstrating characteristic peptidomic patterns of many diseases, including various types of cancer [19][20][21]. Furthermore, it has been shown that peptidomic analyses can detect statistically significant differences observed in bottom-up proteomics [22].…”
Section: Introductionmentioning
confidence: 98%
“…The peptidome -consisting of thousands of peptides: remnants of protein degradation; specific precursor-derived peptides such as hormones, cytokines, or growth factors; and translation products of small open reading frames (smORFs) [16] responds dynamically to changes in the body, providing a rich source of potential biomarkers. This results in the rapid expansion of peptidomics research observed in recent years [17,18], demonstrating characteristic peptidomic patterns of many diseases, including various types of cancer [19][20][21]. Furthermore, it has been shown that peptidomic analyses can detect statistically significant differences observed in bottom-up proteomics [22].…”
Section: Introductionmentioning
confidence: 98%
“…Beyond clinical applications, another attraction of the sHLA immunopeptidome is that it can serve as an unlimited source of native immunopeptides from diverse HLA backgrounds. As importantly, an extensive repertoire of sHLA peptides from a diversity of healthy donors could potentially serve as a resource to improve the general knowledge about peptide processing and presentability ( 10 , 11 ). In contrast, due to limited analytical sensitivity and tissue accessibility mHLA data is currently restricted to a few hundred different alleles, with on average around 5000 up to 160,000 (HLA-A0201) associated MHC peptides identified by mass spectrometry ( 12 ).…”
mentioning
confidence: 99%